Report on Proceedings of the Eighth Annual European CME Forum, Manchester, UK, November 2015. Issue 1 (1st January 2016) - Murray, Ron
Abstract : Delegates from Europe, Asia, and North America attended the Eighth European CME Forum in Manchester, UK, on 12 and 13 November 2015. A new format that included three separate workshop tracks was introduced. The workshops focused on standards and accreditation, education and partnerships, funding and practice in CME/CPD. Discussion and interactive sessions on accreditation issues, inter-professional education, backwards planning, and patient engagement were among the topics addressed. Facilitated conversations were conducted with European leaders in the medical profession and a representative from a European commercial supporters' organisation. Panel discussions on current and future trends and the views of local junior doctors representing the learner community were also conducted.